Assemblr Edu Berbasis Augmented Reality sebagai Medium Komunikasi Digital Interaktif pada Siswa Sekolah Dasar - Wijaya, Abung Supama; Nur Amimatusholihah, Fairus (JURNAL KOMUNIKATIO, 2025)
This study investigates the effectiveness of Assemblr Edu, an augmented reality (AR) application, as a digital communication medium for enhancing elementary students’ conceptual understanding of science. The research was conducted with 22 fifth-grade students at SDN Ciapus 05, Bogor, using a pre-experimental one-group pretest–posttest design. Data were collected through tests, observations, and documentation to capture both quantitative outcomes and qualitative responses. The pretest results revealed an average score of 48.5, with only 27% of students reaching the minimum mastery criterion. Following the AR-based treatment, the posttest average increased significantly to 78.2, with 86% of students surpassing the criterion. The normalized gain (N-Gain) score of 0.52 indicated a medium category improvement, confirming the measurable impact of AR on learning performance. Beyond numerical gains, students demonstrated enthusiasm, curiosity, and active participation in group discussions while exploring three-dimensional models of the human ear. These findings validate the relevance of multimedia learning principles and the Cognitive-Affective Model of Immersive Learning, which emphasize the synergy of visual-verbal channels and the motivational role of immersive media. In conclusion, Assemblr Edu contributes positively not only to science education but also to the broader field of digital communication and media by bridging abstract concepts into tangible experiences. This research offers theoretical reinforcement for interactive communication models and practical recommendations for educators and communication practitioners seeking to integrate AR into diverse learning and public communication contexts.